Improved wheel-rail system of Sweden’s iron ore line - Asplund, Matthias; Khan, Saad Ahmed; Nordmark, Thomas (Luleå tekniska universitet, Drift, underhåll och akustik, 2017)
ABSTRACT: The Swedish Iron Ore Line (IOL) is the only heavy haul line in Europe. The northern part of the line is located above the Arctic Circle, a very harsh climate. Because of the introduction of new vehicles with a 30-tonnes axle load, the track were gradually replaced between 2006 and 2009 with heavier rails, mostly with a steel grade of R350LHT. Just after the first replacement of track in 2006, the project presented herein was established with the primary goal of improving the life length of the rail, and monitoring activities started. This project now has a unique database of rail degradation data. So far, the information has been used to improve the performance of the wheel-rail system and thus extend the life length of the rail, as well as to improve our knowledge of heavy haul operations in a cold climate. The paper discusses the project progress in general and gives some examples of improvements that have been successfully implemented, such as new rail profiles and a higher grinding frequency. Finally, it discusses the challenges of future capacity improvements, such as an increase in the axle load, and how these can be addressed.